Climate change: Comparing “green” and “polluting” nation-states - Posocco, Lorenzo; McNeill, John R. (Frontiers in Sociology, 2023)
Some nation-states, i.e. Norway, Sweden and Denmark, repeatedly score the highest in environmental indicators such as the Environmental Performance Index (EPI) and the Climate Change Performance Index (CCPI). Their cities win environmental awards; they have well developed recycling systems; they perform well with biodegradable waste; and their citizens show awareness of environmental problems, protesting publicly and even sueing their governing bodies if they don’t do the same. For these and other reasons, recent scholarship defined these countries as “exemplary” green nation-states. The question is, which factors pushed them towards the green transition faster than others? And overall, what stops top polluting countries such as China, the United States and Russia from walking the same path? This article attempts to answer these questions by looking at climate change through a theoretical framework based on theories of nationalism and case studies of green nation-states. It compares three of said top polluting countries, China, the United States, and Russia, with “exemplary” green nation-states, and suggests that the pace of greener nation-states rests on 1) a tradition of ecologism and environmentalism rooted in the long run, 2) the lock in of “green nationalism”, a form of nationalism grounded on sustainability, 3) free and effective environmental movements, 4) inclusivity and welfare, and 5) a sense of national pride in environmental achievements. The available evidence seems to suggest that top polluting nation-states lack one or more of these factors.